0563 Association between actigraphic sleep measures and lymphocyte subsets in people with chronic HIV infection. (25th May 2022) - Sharma, Malvika; Borker, Priya; Macatangay, Bernard; Punjabi, Naresh; Rinaldo, Charles; Wolinsky, Steven; Cho, Joshua Hyong-Jin; McKay, Heather; Patel, Sanjay
Abstract: Introduction: While inadequate sleep is known to increase inflammation in immunocompetent individuals, it is unknown if poor sleep worsens inflammation in people living with HIV. The ratio of CD4+/CD8+ T cells is a readily derived measure of chronic inflammation in people living with HIV. We sought to investigate the association between lymphocyte subsets and actigraphy-derived sleep measures in a cohort of HIV seropositive men. Methods: HIV seropositive men on antiretroviral therapy for > 1 year and with undetectable (< 20 copies/mL) plasma HIV-1 RNA participating in the Multicenter AIDS Cohort Study underwent a sleep evaluation with 1 week of wrist actigraphy. Data from 287 participants with ≥ 5 days of actigraphy were analyzed. We evaluated three dimensions of sleep: mean nocturnal sleep duration, sleep onset latency, and sleep maintenance efficiency. Linear regression was used to assess the association between each sleep dimension with CD4+ and CD8+ T-cell counts. Because of a U-shaped association, nocturnal sleep duration was also modelled dichotomously as a normal (6-8 hrs) vs. abnormal duration (<6 or >8 hrs). Results: Participants had a mean (±SD) age of 55 ± 12 years, mean CD4+ count of 723 ± 293 cells/ml, and 7.0 ± 1.7 days of actigraphy data. None of the sleep measures were associated with CD4+ counts. However, participants with abnormal sleep duration had 129 ± 31 cells/mL higher CD8+ counts compared to those with normal sleep duration (p=0.01). There were also nonsignificant trends whereby every 30-minute increase in sleep latency was associated with a 138 cells/ml increase in CD8+ count (p=0.07) while every 10% reduction in sleep efficiency was associated with a 56 cells/ml increase in CD8+ count (p=0.12). These findings were unchanged after adjusting for age and body mass index. Conclusion: Among men with treated HIV infection, abnormal sleep duration (both short and long) is associated with increased circulating CD8+ T cell count, suggesting increased chronic inflammation. Support (If Any): NIH AI0355041, HL082610 and American Thoracic Society ASPIRE Fellowship